Annual release of selected UV filters via effluent from wastewater treatment plants in Australia. (May 2020) - O'Malley, Elissa; O'Brien, Jake W.; Verhagen, Rory; Mueller, Jochen F.
Abstract: Studies conducted globally have identified wastewater effluent as a key source of UV filters released into the aquatic environment. We assessed the annual release of UV filters from wastewater treatment plant effluent in Australia and evaluated the removal of these chemicals during wastewater treatment. Effluent samples were collected from 33 sites alongside matching influent samples. Sample collection predominately occurred during the Australian Census in August 2016, which allowed for accurate per capita normalisation of the results. A subset of sites was also sampled over the Southern Hemisphere summer (December–February) period. Five UV filters were detected with at least one detected in 95% of effluent samples. The summed concentration of UV filters ranged from 130 ng L −1 to 8400 ng L −1 and averaged 2800 (±1900) ng L −1 . Of the target UV filters, 2-phenylbenzimidazole-5-sulfonic acid (PBSA) and benzophenone 4 (BP4) showed the lowest removal efficiencies (11 ± 36% and 51 ± 43%, respectively) across all sites and were the most abundant in effluent. Average estimated removal efficiencies of the other compounds were between 59 (±24) % (4-methylbenzylidene camphor (4-MBC)) and 74 (±22) % (benzophenone 1 (BP1)). We did not find a trend in seasonal differences in the per capita release of UV filters in effluent samples. We estimate that approximately 40% of UV filter loads measured in influent are breaking through to the effluent resulting in the release of approximately 20 kg day −1 of the selected UV filters into the aquatic environment from treated wastewater effluent in Australia. Graphical abstract: Image 1 Highlights: 96% of Australian wastewater effluent samples contained either PBSA or BP4. Summed UV filter concentrations in wastewater effluent averaged 2.8 ± 1.9 μg L −1 Removal efficiencies were highly variable between sites (eg. PBSA mean 11 ± 36%). Australian wastewater effluent releases an estimated 20 kg day −1 of five UV filters. Higher average BP4 per capita loads compared to international studies.